The effect of exposure to media campaign messages on adult cessation. (October 2015) - Nonnemaker, James M.; Dench, Daniel; Homsi, Ghada; MacMonegle, Anna; Duke, Jennifer
Abstract: Introduction: Numerous studies have examined the relationship between antitobacco mass-media campaigns and quit attempts. However, less is known about the effect of these campaigns on relapse. This paper evaluates the effect of media exposure on smokers' quit attempts and relapse. Methods: We used data from the Florida Adult Cohort Survey, a telephone follow-up survey of adult smokers and recent quitters, who completed the Florida Adult Tobacco Survey. For this study, 1823 unique smokers and recent quitters from baseline first observed between July 2008 and October 2012 were surveyed through up to seven follow-up interviews between October 2009 and October 2013. Media exposure during this period primarily represents exposure to Florida's Tobacco Free Florida (TFF) campaign, although it also includes exposure to the Centers for Disease Control and Prevention's Tips From Former Smokers media campaign in 2012–2013. A multiple-spell discrete-time survival model was estimated using logistic regression. Each spell represents a quit attempt or relapse event. Results: The odds of the first observed quit attempt are higher at higher levels of target rating points (TRPs) (aOR = 1.02, p  = 0.023). The odds ratio for relapse and second quit and second relapse was not statistically significant. Conclusions: The results suggest that exposure to media campaign messages in Florida has led to increases in quit attempts. Although the estimates were not statistically significant for relapse or the second spell of quit attempts or relapse, the results suggest that media messages might also influence subsequent quit attempts or relapses after an initial quit attempt. Highlights: Studies have examined the effect of cessation media campaigns on quit attempts Few studies have examined the effect of cessation media campaigns on relapse We examine the effect of media exposure on smokers' quit attempts and relapse Exposure to cessation media messages in Florida led to increases in quit attempts Exposure to cessation media messages may also influence relapse